Development of Interactive Digital Textbook Based on STEM to Enhance Junior High School Students' Critical Thinking Skills in Environmental Pollution Subject - Nor Indri Yanti; Imam Mudakir; Sulifah Aprilya Haryani (BIOEDUKASI, 2023)
The purpose of this research is to describe the stages of developing an interactive digital textbook based on STEM for the subject of environmental pollution, and to test the effectiveness of the interactive digital textbook based on STEM in enhancing the critical thinking skills of junior high school students in the subject of environmental pollution. This research is a development research that adopts the 4 D model from Thiagarajan's, which consists of four stages, namely define, design, develope, and disseminate (Mutia, 2020). The research subjects were junior high school students who had never received environmental pollution material. Limited-scale trials and single-class trial were conducted at Ma'arif 08 Junior High School in Wuluhan Jember. Dissemination was carried out at Ma'arif Ambulu Islamic Junior High School and Darul Hikam Islamic Junior High School This research used qualitative and quantitative approaches. STEM-based interactive digital textbooks on environmental pollution material are effective in improving critical thinking skills with an average score of 89.03 based on indicators of providing simple explanations, providing further explanations, developing strategies and tactics, and students' ability to draw conclusions.